ESTIMASI VOLUME SEDIMEN LAHAR DINGIN DI SEBAGIAN KALI GENDOL GUNUNG MERAPI MENGGUNAKAN FOTO UDARA FORMAT KECIL DAN LIDAR - , BELINDA DUHITA P ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Beside supplies natural resources potential, Merapi Mount also produces natural disasters. One of them is eruption which produces primary and secondary risks. Secondary risk or following risk as a mud flow happened after eruption when rain fell on mount peak. Rain water in current river bring so much materials from mount peak until sediment made. These sediment need to be measured to get the mud flow volume information. The aims of this research were: (1) to take the topographic information as Digital Elevation Model (DEM) especially Digital Surface Model (DSM) from small format aerial photograph (SFAP) by using photographic remote sensing application and GIS, (2) to take accuration rate from DEM (DSM) SFAP, (3) to estimate mud flow sediment volume in a part of Kali Gendol with before and after DEM by also using application small format remote sensing and GIS. Creating DEM through small format aerial photograph (SFAP) pass some digital photogrammetric processes. Basically, digital photogrammetric process are similar with conventional photogrammetric process except by considering also lens distortion. Digital photogrammetric processes to make DEM and its accuracy are flying lines reconstruction, GCP identification (it means donât need SFAP registration), camera calibration, inner orientation, tie points (same points in some photos) identification, absolute orientation, creating DEM, and DEM accuracy test. Sediment volume was made by processing LiDAR DEM first until profiles compared to calculate volume through pre (from SFAP) and post eruption.SFAP DEM has 5 m in resolution while it has 12,9 m in horizontal accuracy and 17,51 m in vertical accuracy. Through FUFK-DEM and LiDAR-DEM, we get 23 polygons calculated by cut and fill process to get sediment material volume. Total adding sediment volume is 4.96 million mÂ³, total removal sediment volume is 4,96 million mÂ³, while final total volume after calculated is 0,31 million mÂ³ along the river.